Analisis Pengaruh Service Quality dan Corporate Image Terhadap Customer Satisfaction Serta Implikasinya Terhadap Customer Loyalty pada Konsumen Restoran Meradelima di Jakarta Selatan - Senja Dara Fika Saputri (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to determine whether or not the influence of service quality, corporate image and customer satisfaction on purchasing decisions at Meradelim RestaurantBrand image and brand trust are factors that can influence consumer purchasing decisions. A good service quality will have a positive impact on the company which will ultimately benefit the company through increased consumer purchases of products or services.This study uses a sample and a population of 110 respondents who are cutomer at Meradelima Restaurant, using purposive sampling method. The results showed that service quality, corporate image and customer satisfaction had a positive and significant effect on purchasing decisions.